2021
DOI: 10.1021/acsami.1c00565
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Probing of Mass Exchange at the Solid Electrolyte Interphase in Aqueous and Nonaqueous Zn Electrolytes with EQCM-D

Abstract: Multivalent chemistry provides intriguing benefits of developing beyond lithium ion energy storage technologies and has drawn extensive research interests. Among the multivalent candidates, metallic zinc anodes offer an attractive high volumetric capacity at a low cost for designing the secondary ion batteries. However, the interfacial mass exchange at the Zn electrolyte/anode boundary is complicated. The least understood solid electrolyte interphase (SEI) occurs simultaneously with the reversible metal deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 70 publications
0
17
1
Order By: Relevance
“…Moreover, it was reported that the aqueous ZnCl 2 electrolyte exhibited reversible Zn electrodeposition, while the nonaqueous Zn(TFSI) 2 organic electrolyte system showed complex interfacial reactions which result in the formation of an ionically permeable SEI layer with rich content of organic S and N components at initial electrochemical cycles (Figure 4c), leading to the high Coulombic efficiency of the organic electrolyte. [91] Although the electrochemical window (3.0 V) of Zn(TFSI) 2 organic electrolytes is limited by the poor oxidation stability compared with other zinc salts, it can still satisfy most high voltage cathode materials. For instance, as shown in Figure 5a, Zhang et al reported high-voltage Zn/graphite battery with 1 m Zn(TFSI) 2 /AN organic electrolyte exhibited the highest average output voltage of 2.2 V (Figure 5b), which is mainly attributed to electrolytes with high oxidative/reductive stability enabling good compatibility with the graphite cathode.…”
Section: Salts For Conventional Organic Electrolytesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it was reported that the aqueous ZnCl 2 electrolyte exhibited reversible Zn electrodeposition, while the nonaqueous Zn(TFSI) 2 organic electrolyte system showed complex interfacial reactions which result in the formation of an ionically permeable SEI layer with rich content of organic S and N components at initial electrochemical cycles (Figure 4c), leading to the high Coulombic efficiency of the organic electrolyte. [91] Although the electrochemical window (3.0 V) of Zn(TFSI) 2 organic electrolytes is limited by the poor oxidation stability compared with other zinc salts, it can still satisfy most high voltage cathode materials. For instance, as shown in Figure 5a, Zhang et al reported high-voltage Zn/graphite battery with 1 m Zn(TFSI) 2 /AN organic electrolyte exhibited the highest average output voltage of 2.2 V (Figure 5b), which is mainly attributed to electrolytes with high oxidative/reductive stability enabling good compatibility with the graphite cathode.…”
Section: Salts For Conventional Organic Electrolytesmentioning
confidence: 99%
“…[ 97 ] The reason of this phenomenon was demonstrated to be related to the adhesion of TFSI − on the surface of the electrode in Zn(TFSI) 2 electrolyte. [ 91 ] Naveed et al. developed an organic electrolyte composed of Zn(OTf) 2 , TMP, and DMC, as shown in Figure , which shows highly reversible Zn plating/stripping without any dendritic growth on Zn anode after plating/stripping for 1000 cycles (2000 h).…”
Section: Organic Electrolytes For Zibsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 The formation of an ionically permeable SEI layer has been confirmed in the Zn 2+ -based electrolyte/electrode interface in previous literature. 12 However, as far as we know, in situ EQCM has not been performed during the investigation of the Al 3+ -based electrolyte for electrochromic batteries or devices.…”
Section: Introductionmentioning
confidence: 99%